Menangkal Ujaran Kebencian Digital melalui Etika Komunikasi Al-Qur'an: Telaah atas Q.S. al-Ḥujurāt (49): 11 - widiawati; Achmad Abubakar; Rahmi Damis (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2026)
The widespread prevalence of digital hate speech, cyberbullying, negative labeling, and identity-based polarization has exposed the growing crisis of ethical communication in contemporary social media. While Islamic communication ethics has been widely discussed, relatively few studies have examined how Qur'anic exegesis can provide a comprehensive ethical framework for addressing these digital challenges. This study aims to investigate how Q. al-Ḥujurāt (49):11 articulates Qur'anic communication ethics and to explore its relevance for countering hate speech in digital environments. Employing qualitative library research with the tahlili method of Qur'anic exegesis, the study analyzes the verse through linguistic (mufradāt), historical (asbāb al-nuzūl), textual (munāsabah), and comparative interpretive approaches based on classical and contemporary Qur'anic commentaries. The findings identify five interconnected ethical principles: respect for human dignity, self-reflection and communal solidarity, prevention of reciprocal hostility, faith-based moral self-regulation, and the promotion of brotherhood and tolerance. Collectively, these principles provide a normative foundation for preventing cyberbullying, digital backbiting, identity-based hate speech, negative labeling, and social polarization across social media platforms. This study contributes to contemporary Qur'anic studies by demonstrating how Q. al-Ḥujurāt (49):11 offers a coherent ethical framework for countering digital hate speech, thereby strengthening interdisciplinary engagement between Qur'anic ethics, digital communication, and responsible online citizenship.